1996
DOI: 10.1002/(sici)1098-2744(199601)15:1<57::aid-mc8>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin expression in human prostate carcinoma

Abstract: The metalloproteinases, a multigene family of metal-requiring enzymes, have been suggested to play a role in tumor invasion and metastasis. Previously, we demonstrated that human primary prostate tumors express higher levels of matrilysin and gelatinase A mRNA than normal prostate does. In the study presented here, we used in situ hybridization and immunohistochemical staining of serial sections of paraffin-embedded primary prostate tumors to compare the sites of matrilysin and gelatinase A expression and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 24 publications
(17 reference statements)
2
42
0
Order By: Relevance
“…However, no studies have elucidated the molecular mechanism regulating MMP-7 localization to the basal epithelial compartment or the depolarized diffuse cytoplasmic distribution of MMP-7 in adenocarcinoma cells at the invasive front. Similar to other MMPs such as MMP-2, the activated form of MMP-7 is readily detected within both carcinoma 11,17 and normal intestinal tissues. 6 Our previous in vitro biochemical studies have shown that proMMP-7 is fully activated by treatment with trypsin or MMP-3, and partially with plasmin or leukocyte elastase.…”
mentioning
confidence: 82%
“…However, no studies have elucidated the molecular mechanism regulating MMP-7 localization to the basal epithelial compartment or the depolarized diffuse cytoplasmic distribution of MMP-7 in adenocarcinoma cells at the invasive front. Similar to other MMPs such as MMP-2, the activated form of MMP-7 is readily detected within both carcinoma 11,17 and normal intestinal tissues. 6 Our previous in vitro biochemical studies have shown that proMMP-7 is fully activated by treatment with trypsin or MMP-3, and partially with plasmin or leukocyte elastase.…”
mentioning
confidence: 82%
“…34 This has been observed in adenomas or premalignant lesions of the intestine, stomach, prostate, breast and ovary. [51][52][53][54][55][56] We observed low levels of MMP7 in normal human lung epithelial cells, while the expression increased in premalignant and neoplastic cells. Using genetically manipulated animals, a definite role for MMP7 in early tumor development has been established.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated by in situ hybridization that the overexpression of matrilysin mRNA is confined to the epithelial cells of these structures and is not present in the surrounding stroma or infiltrating leukocytes (12). Immunohistochemical analysis confirmed that the expression of matrilysin mRNA in the prostate epithelium correlates with the expression of matrilysin protein.…”
mentioning
confidence: 79%
“…In the normal prostate, we have observed that inflamed ductule and acinar epithelia frequently express high levels of matrilysin (11,12). It has been clearly demonstrated by in situ hybridization that the overexpression of matrilysin mRNA is confined to the epithelial cells of these structures and is not present in the surrounding stroma or infiltrating leukocytes (12).…”
mentioning
confidence: 98%